Discovering a New Okadaic Acid Derivative, a Potent HIV Latency Reversing Agent from Prorocentrum lima PL11: Isolation, Structural Modification, and Mechanistic Study - Dong Huang; Lian-Shuai Ding; Fang-Yu Yuan; Shu-Qi Wu; Han-Zhuang Weng; Xiao-Qing Tian; Gui-Hua Tang; Cheng-Qi Fan; Xiang Gao; Sheng Yin (Marine Drugs, 2023)
Marine toxins (MTs) are a group of structurally complex natural products with unique toxicological and pharmacological activities. In the present study, two common shellfish toxins, okadaic acid (OA) (1) and OA methyl ester (2), were isolated from the cultured microalgae strain Prorocentrum lima PL11. OA can significantly activate the latent HIV but has severe toxicity. To obtain more tolerable and potent latency reversing agents (LRAs), we conducted the structural modification of OA by esterification, yielding one known compound (3) and four new derivatives (4–7). Flow cytometry-based HIV latency reversal activity screening showed that compound 7 possessed a stronger activity (EC50 = 46 ± 13.5 nM) but was less cytotoxic than OA. The preliminary structure–activity relationships (SARs) indicated that the carboxyl group in OA was essential for activity, while the esterification of carboxyl or free hydroxyls were beneficial for reducing cytotoxicity. A mechanistic study revealed that compound 7 promotes the dissociation of P-TEFb from the 7SK snRNP complex to reactivate latent HIV-1. Our study provides significant clues for OA-based HIV LRA discovery.